PENGARUH KUALITAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) TERHADAP KEPUASAN MASYARAKAT PADA KANTOR CAMAT KECAMATAN SEBERANG ULU DUA KOTA PALEMBANG - Achmad, Achmad (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
This study is to find out how the quality of service provided by PATEN employees at the sub-district office across Ulu Dua Palembang to the community who perform services and to test how much influence service quality has on community satisfaction at PATEN at the Seberang Ulu Dua District office, Palembang City. The research method used is associative quantitative method, which is a method that aims to determine the relationship between two or more variables. Data analysis was performed using a simple regression test, t test, analysis of the coefficient of determination test. Based on the results of research and discussion, it can be concluded that there is an influence of service quality that has a positive and significant effect on community satisfaction. This is based on the results of the analysis of the T test obtained that T count is greater than T table, namely 3.288 2.00324 and the value of Sig is 0.002 0.05. Thus it can be stated that there is a positive and significant relationship or influence between service quality and community satisfaction. As for the percentage of the influence of service quality on community satisfaction, it was obtained based on the results of the analysis of the coefficient of determination, the R Square value of 0.162 x 100% = 16.2% which means that the effect of service quality on community satisfaction is 16.2% which means that it has a significant relationship or influence still low.Keywords: Service Quality, Community Satisfaction, District Integrated Administrative Services